Synergetic control for HVAC system control and VAV box fault compensation - Ettouil, Radhia; Chabir, Karim; Sauter, Dominique; Abdelkrim, Mohamed Naceur (Zielona Góra: Uniwersytet Zielonogórski)
Synergetic control is proposed for heating, ventilating and air-conditioning (HVAC) system control. The synergetic controller is developed using the nonlinear model of the HVAC system. Occupancy information in each zone is required in the design of the controller which offers inherent comfort according to the occupancy in the zone. The stability of the building system using the proposed control is verified through the Lyapunov approach. It is also proved that the synergetic controller is robust to external disturbances. Then, synergetic theories are used to design a reconfigurable control for damper stuck failures in variable air volume (VAV) to recover the nominal performance. Simulations are provided to validate the effectiveness of the proposed controller for a three-zone building.
Keywords: HVAC system; synergetic control; reconfigurable control; robustness